Mineral nutrition of peach palm seedlings under different salinity levels - Fernandes, Antonio Rodrigues; de Carvalho, Janice Guedes; Curi, Nilton; Pinto, José Eduardo Brasil Pereira; Guimarães, Paulo de Tácito Gontijo (Pesquisa Agropecuaria Brasileira, 2002)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The productive potential of plants may be affected by nutritional disorders induced by saline stress. The objective was to study the influence of different salinity levels on mineral nutrition of peach palm (Bactris gasipaes H.B.K.) seedlings in greenhouse conditions with nutritive solution. The experimental design was in randomized blocks, with seven treatments and four replications. The treatments consisted of the following dosages (mmol L-1): 0.0 of Na and 0.5 of Cl; 1.0 of Na and 0.5 of Cl (control); and 5.0, 15.0, 30.0, 60.0 and 120.0 of NaCl. The content of the macronutrients varied with the salinity, there was reduction of P and K in the roots, K and Ca in the leaves, and S in different parts of the plants. Therefore, there was increase of Na and Cl in different parts of the plant. The enhancement of the ratios Na/K, Na/Ca, Na/Mg, Cl/N, Cl/P and Cl/S induced a nutritional imbalance in the plant.